(untitled) (Global Journal of Human-Social Science, 2025)
The region of Thrace in the Aegean is an example of the dynamics of contact between Greeks and local populations The region was chosen because of the need to understand the social cultural and religious dynamics in the hybrid sanctuaries sphere in the Northern Aegean through material culture We will present preliminary reflections on the issue of insularity in cult contexts in the formation of a regional and or local koin in the Northern Aegean of the Archaic period in the sphere of the Northern Aegean pera ai The socalled glocalism immersed in contact networks creates a bond of isolation and non-isolation between the islands and mainland For this proposal will be present specifically the sanctuaries of hybrid deities founded by Greek Thassos Island